The Role of Marketing Capability in the Relationship between Entrepreneurial Orientation and Marketing Performance: A Study of Batik SMEs in Ciayumajikuning - Rois, Tatang; Arraniri, Iqbal; Akbar, Ilham; Nurhayani, A'i; Pratiwi, Erni Yuliyanti (Airlangga Journal of Innovation Management, 2025)
Previous studies on the influence of entrepreneurial orientation on marketing performance have revealed inconsistencies. To address these discrepancies, a new research model was developed, placing marketing capability as a mediating variable. The study is also based on the challenges that SMEs face in improving their marketing performance. This quantitative study uses a survey method to examine batik SMEs in the Ciayumajakuning region of West Java, Indonesia. The sample size consists of 200 SME owner-managers, selected using disproportionate random sampling. Data analysis was conducted using structural equation modelling with the AMOS program. The results indicate that marketing capability mediates the influence of entrepreneurial orientation on marketing performance. These findings are significant in that they identify a research model that addresses the challenges faced by SMEs in improving their marketing performance by focusing on market orientation and the role of marketing capability as a mediator. The results of this study have practical implications for SMEs in the batik industry in the Ciayumajakuning region, helping them to overcome problems with marketing performance by adopting a market-oriented approach.